2020
DOI: 10.1038/s41598-020-74988-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentations, laboratory and radiological findings, and treatments for 11,028 COVID-19 patients: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis investigated the comorbidities, symptoms, clinical characteristics and treatment of COVID-19 patients. Epidemiological studies published in 2020 (from January–March) on the clinical presentation, laboratory findings and treatments of COVID-19 patients were identified from PubMed/MEDLINE and Embase databases. Studies published in English by 27th March, 2020 with original data were included. Primary outcomes included comorbidities of COVID-19 patients, their symptoms pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 116 publications
9
39
0
Order By: Relevance
“…During this first phase, about five days after infection, patients suffer from substantial viral replication [ 75 ]. During this phase, the primary symptoms are mostly fever (88.7%), coughing (57.6%), and dyspnea (45.6%) [ 14 , [75] , [76] , [77] ]. Other common symptoms include malaise (29.6%), fatigue (28.2%), neurological symptoms (20.8%), myalgia (16.9%), headaches, diarrhea, and anosmia [ 14 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…During this first phase, about five days after infection, patients suffer from substantial viral replication [ 75 ]. During this phase, the primary symptoms are mostly fever (88.7%), coughing (57.6%), and dyspnea (45.6%) [ 14 , [75] , [76] , [77] ]. Other common symptoms include malaise (29.6%), fatigue (28.2%), neurological symptoms (20.8%), myalgia (16.9%), headaches, diarrhea, and anosmia [ 14 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…According to a systematic review by Rodriguez and coworkers, the most prevalent changes in laboratory parameters are decreased albumin (75.8%), increased C-reactive protein levels (58.3%), followed by high lactate dehydrogenase levels (57.0%), and lymphopenia (43.1%) [ 76 ]. Furthermore, laboratory features that are typically abnormal in patients suffering from severe COVID-19 include elevated D-Dimer levels, ferritin, and Interleukin (IL)-6 levels, elevated cardiac biomarkers, and hepatic enzymes [ 11 , 77 , 80 , 81 ]. In cases where bacterial superinfection is suspected, procalcitonin might be helpful in addition to microbiological sampling, bronchoalveolar lavage, and galactomannan testing for fungal infection/aspergillosis [ 82 , 83 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Multivariate analysis revealed that at the hospital's point of admission, pneumonic changes in chest radiograph were suggestive of bacterial co-infection among the COVID-19 patients and demands prudent use of antimicrobials 54 . Similarly, multiple research studies revealed that only those COVID-19 patients with radiologically identified bilateral pulmonary infection required antimicrobials therapy [55][56][57][58][59][60] . The current US guideline does not recommend the empiric use of antimicrobials in COVID-19 if not supported by documentary evidence of secondary bacterial or fungal infections 55 .…”
Section: " Sir Alexander Flemingmentioning
confidence: 99%
“…Conforming to the observation that COVID-19 tends to be mild in children, the clinical classifications range from asymptomatic to moderate, with symptoms no worse than a slight fever and a running nose. Regardless, half of the patients displayed abnormal chest imaging results, notably the ground-glass opacities frequently also described in adults [ 41 ].…”
Section: Spotlight On Original Articlesmentioning
confidence: 99%